Performance evaluation of porous asphalt mixtures modified with basalt fiber - Çetín, Altan; Oral, Gokhan (Revista de la Construcción. Journal of Construction, 2022)
Porous pavement applications, which is environmentally friendly, especially for residential areas, allow rainwater to remain clean and to feed groundwater through infiltration. Porous asphalt pavements, in which are among the pavement types used in porous pavements systems, also reduce environmental noise pollution. On the other hand, there is a need to improve the performance of these asphalt pavement mixtures, which have a short service life due to their porous structure. It has been considered to improve the performance of the pavement mixtures by using basalt fiber without compromising the hydraulic permeability level. The waste slag material released during the ferrochrome production process was used as aggregate in the porous asphalt mixture design. Thus, it is aimed to benefit from the economic and environmental aspects with the recycling of ferrochrome slag in an area suitable for its properties. In the study, the design performances of porous asphalt mixtures were determined with tests such as volume analysis, permeability, Cantabro particle loss, indirect tensile strength, and moisture susceptibility. Basalt fiber was added at 0.2%, 0.4%, 0.6% and 0.8% of the mixture weight. It has been determined that the mixtures of basalt fibers at 0.2% significantly improve the mechanical performance.